Outcome Of Surgical Treatment Of Tuberculosis Of The Spine In Patients With Motor Deficits - Flamerz, Bassam Mahmood (AL-Kindy College Medical Journal, 2019)
Background: Significant numbers of patients with spinal tuberculosis (TB), especially in developing countries, still present late after disease onset with severe neurological deficits.Objective:This study was conducted to assess the outcome of surgery in patients with tuberculosis of the spine with motor deficits.Type of the study: Retrospective study.Methods: We retrospectively analyzed data obtained in all the patients with severe motor deficits due to spinal TB admitted to and surgically treated in four hospitals in Baghdad/Iraq during the period from January 2012 to January 2014. History, examination, imaging, histological, postoperative, and follow-up data were retrospectively culled from hospitals records and then analyzed.  Data obtained in 48 patients with 6-24 months of follow up (mean follow-up period 12.8 months) were analyzed. The disease in 34 patients was characterized by Frankel Grade A/B and in 14 patients by Frankel Grade C at admission.Results: Thirty (88%) of the 34 patients with Frankel Grade A/B status and 13 (92.8%) of the 14 patients with Frankel Grade C status at admission experienced improvement to Frankel Grade D/E (walking with or without support) at the last follow-up examination after surgery. The degree of improvement exhibited by patients with a Frankel Grade A/B spinal cord injury was comparable to that shown by patients with Frankel Grade C status. Even patients with flaccid paraplegia, gross sensory deficit, prolonged weakness, spinal cord signal changes demonstrated on magnetic resonance imaging, and bladder involvement have experienced dramatic improvement in motor function since surgery. A significant number of the patients have shown remarkable improvement in other symptoms such as pain (91.6%), spasticity (88%), and bladder symptoms (88%).Conclusions: A significant proportion of patients with spinal TB and severe motor deficits experience remarkable improvement after surgical decompression and hence should undergo surgery even though they may be suffering from paraplegia of considerable duration